Lead optimization of cathepsin K inhibitors for the treatment of Osteoarthritis. (15th October 2022) - Ginnetti, Anthony T.; Paone, Daniel V.; Nanda, Kausik K.; Li, Jing; Busuek, Marina; Johnson, Scott A.; Lu, Jun; Soisson, Stephen M.; Robinson, Ronald; Fisher, John; Webber, Andrea; Wesolowski, Gregg; et al.
Graphical abstract: Abstract: Cathepsin K (Cat K) is a cysteine protease involved in bone remodeling. In addition to its role in bone biology, Cat K is upregulated in osteoclasts, chondrocytes and synoviocytes in osteoarthritic (OA) disease states making it a potential therapeutic target for disease-modifying OA. Starting from a prior preclinical compound, MK-1256, lead optimization efforts were carried out in the search for potent Cat K inhibitors with improved selectivity profiles with an emphasis on cathepsin F. Herein, we report the SAR studies which led to the discovery of the highly selective oxazole compound 23, which was subsequently shown to inhibit cathepsin K in vivo as measured by reduced levels of urinary C-telopeptide of collagen type I in dog.